Bali Traditional Architecture: Sustainability from the Perspective of Capital Concept - I Putu Gede Suyoga; Made Adi Widyatmika; Ni Ketut Ayu Juliasih (International Journal of Interreligious and Intercultural Studies, 2020)
This study aims to reveal the sustainability of Balinese traditional residential architectural practices which are based on the provisions of traditional ethnic Balinese social stratification and refers to the capital ownership in Generative Structural Theory from Pierre Bourdieu (economic, cultural, social and symbolic). At present, there are dynamics ownership and capital conversion in the traditional social strata which affect the sustainability of traditional residential architecture practices. The traditional Balinese residential architecture in this study is understood to be the spatial layout and traditional residential buildings of the Middle Bali era. Its sustainability today is seen from the concept of capital in the perspective of Bourdieu’s theory. The basic assumption of Bourdieu’s theory is basically that humans are in the field of social struggle to emerge victorious by competing with one another. This study is a qualitative research with interpretative descriptive method. Primary data were obtained from selected informants (purposive) and from field observations, as well as secondary data from the literature. The study findings show that traditional residential architecture practices in the Middle Bali era were strongly influenced by capital ownership (economic, cultural, social, and symbolic) with various forms of conversion to traditional Balinese aristocratic (triwangsa). Development at this time has opened the opportunity to control various capital for ordinary community (jabawangsa), so that the realm of Balinese traditional housing becomes a medium of struggle as well as a symbol of success in social struggle. On the other hand, the contestation of Balinese traditional residential architectural practices is a sustainability in the arena of social struggle within Balinese society today.